2022
DOI: 10.1063/5.0118263
|View full text |Cite
|
Sign up to set email alerts
|

Flexible engineering of circular dichroism enabled by chiral surface lattice resonances

Abstract: Engineering the chiroptical responses of artificial nanostructures is vital for realizing applications in the fields of optical devices, enantioselective separation and bio-sensing. Here, by utilizing the nano-kirigami based meta-molecule arrays, the flexible engineering of circular dichroism (CD) is achieved in the near-infrared wavelength region by the excitation of chiral surface lattice resonances (SLRs). It is found that the chiral SLRs can be flexibly tailored by a tiny structural perturbation. As a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The prospects of these applications have triggered the study and characterization of a variety of periodic arrays supporting chiral lattice resonances. The majority of these arrays are built from the repetition of chiral unit cells, made of either individual nanostructures with complex chiral morphologies, , such as helices, or multiple nanostructures forming a chiral arrangement. , As expected, the lattice resonances supported by these systems exhibit different responses under illumination with right- and left-handed circularly polarized light. More recently, it has been shown that the combination of a rectangular lattice with an achiral unit cell results in arrays capable of supporting lattice resonances with some degree of chirality, which can be enhanced by positioning the array in an inhomogeneous dielectric environment .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The prospects of these applications have triggered the study and characterization of a variety of periodic arrays supporting chiral lattice resonances. The majority of these arrays are built from the repetition of chiral unit cells, made of either individual nanostructures with complex chiral morphologies, , such as helices, or multiple nanostructures forming a chiral arrangement. , As expected, the lattice resonances supported by these systems exhibit different responses under illumination with right- and left-handed circularly polarized light. More recently, it has been shown that the combination of a rectangular lattice with an achiral unit cell results in arrays capable of supporting lattice resonances with some degree of chirality, which can be enhanced by positioning the array in an inhomogeneous dielectric environment .…”
Section: Introductionmentioning
confidence: 92%
“…53−55 The prospects of these applications have triggered the study and characterization of a variety of periodic arrays supporting chiral lattice resonances. 56−64 The majority of these arrays are built from the repetition of chiral unit cells, made of either individual nanostructures with complex chiral morphologies, [56][57][58]63 such as helices, 60 or multiple nanostructures forming a chiral arrangement. 65,66 circularly polarized light.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To explain the emergence of lattice resonances and the characterization of the collective coupling of multipoles inside a lattice, see [66,67], for instance. The asymmetric Fano resonance observed in this spectral range in the circular dichroism spectra indicates an interference of different competing pathways determining whether the lattice resonance is left-or right-handed and, therefore, also the sign of the circular dichroism, see [61]. Three aspects influence the resonance around 334 nm in the spectra: (i) The chiral response of the MOF material, (ii) the chiral, electric, and magnetic dipole moments of the isolated MOF cylinders, and (iii) the lattice coupling.…”
Section: B Metasurface Made From Uio-67-r-binol Mof Cylindersmentioning
confidence: 83%
“…The possibility of enhancing the circular dichroism of chiral objects by the strong near-fields of plasmonic structures or high-refractive-index dielectric materials as silicon cylinders is well-known [53][54][55][56][57][58][59][60][61][62]. A central quantity in the discussion of this enhancement is the optical chirality density defined as [63]…”
Section: B Metasurface Made From Uio-67-r-binol Mof Cylindersmentioning
confidence: 99%
See 1 more Smart Citation